Late Villafranchian Ursus etruscus and other large carnivorans from the Orce sites (Guadix-Baza basin, Andalusia, southern Spain): Taxonomy, biochronology, paleobiology, and ecogeographical context. (28th February 2017) - Medin, Tsegai; Martínez-Navarro, Bienvenido; Rivals, Florent; Madurell-Malapeira, Joan; Ros-Montoya, Sergio; Espigares, María-Patrocinio; Figueirido, Borja; Rook, Lorenzo; Palmqvist, Paul
Abstract: Dental morphology and tooth microwear studies are used as analytical proxies for understanding the taxonomy, biochronology, paleobiology and ecogeographical context of Early Pleistocene Ursus species ( U. etruscus ) and other large carnivore taxa (Hyaenidae and Canidae) preserved in the Early Pleistocene (Calabrian) sites from Orce (Guadix-Baza basin, Andalusia, Spain), including Venta Micena (VM), Barranco León (BL-D) and Fuente Nueva-3 (FN-3). The results of this study suggest varied dietary habits and behavior among Ursus species and other carnivorous taxa. Morphologically, the bunodont dentition and microwear patterns of Ursus etruscus advanced forms from VM, BL-D and FN-3 indicate their omnivorous feeding ecology, in agreement with the dietary habits of extant brown bear, Ursus arctos (a purported descendant of U . etruscus ). However, in the case of VM isotopic analyses of bioapatite and bone collagen suggest a significant contribution of fish in their diet, as in the case of some populations of modern brown bear, and also a regular consumption of plant tissues, as evidenced by the comparatively high δ 15 N and δ 18 O values in this extinct species, respectively.